Pengaruh Stres Kerja Terhadap Kinerja Karyawan - Nadia Antonita Christy; Sholihati Amalia (Jurnal Riset Bisnis dan Investasi, 2017)
Every employee must have experienced job stress. Work stress can give positive effect but if excessive it will cause negative impact especially is on employee performance. Therefore work stress must be prevented and handled. Excessive job stress is also experienced by employees of production department at PT Catur Kartika Jaya which is engaged in making mosquito nets. Therefore this research was made to find out how the job stress faced by employees of the production of PT Catur Kartika Jaya and its influence on the performance of these employees. The results obtained through this study is that there is a strong and significant negative influence on work stress on the performance of production employee in PT Catur Kartika Jaya. Therefore, the authors suggest the company to do socialization about work stress management and various activities outside the work that can rest and refresh the soul and body.